RANCANG BANGUN MESIN PENCACAH RUMPUT GAJAH UNTUK PROSES PEMBUATAN SILASE PAKAN TERNAK SAPI - Genta Arya Rahma Mahendra, Genta; Wulandari, Diah; Utama, Firman Yasa; Widoretno, Yustin Setiya (Universitas Negeri Surabaya, 2026)
Silage is a method of providing cow feed that requires a forage chopping process so that it is easy to ferment and has a longer shelf life. However, most breeders still do the enumeration manually, so it takes a long time and the size of the enumeration is not uniform. Therefore, this study aims to design an elephant grass chopper with dual input and output funnels, equipped with a knife and a beater to speed up cutting and crush harder materials. This machine is expected to be able to produce a uniform size of 2–5 cm according to the SNI 7785.1:2003 standard This research method uses a 4D Research and Development (R&D) model to design and test a elephant grass chopper. The stages include literature review, design, machine construction and assembly, and then functional testing using elephant grass as the test material in three trials. The test data is analyzed to assess the machine's performance and feasibility. The results of the study show that the designed elephant grass chopper can operate well. Based on the function test at 1500 rpm with a test material load of 5 kg, the machine produces a chopping size of 2–5 cm with a working capacity of 92 kg/hour, so it is considered suitable for use to support the process of making silage for cattle feed and increase efficiency compared to manual methods.